2014
DOI: 10.1159/000366133
|View full text |Cite
|
Sign up to set email alerts
|

Binding Action and Emotion in First-Episode Schizophrenia

Abstract: Background/Aims: Several components of social cognition are compromised in schizophrenia (SCZ) from the early stage of the illness. In this study we first investigated whether mirror neuron-driven embodied simulation (mnES) is altered in first-episode SCZ. Second, we tested whether emotional cues impact on the mnES in SCZ patients. Methods: Twenty-two SCZ patients and 22 healthy controls (HCs) observed goal-related actions in either a neutral or emotional context during functional magnetic resonance imaging sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
0
9
0
1
Order By: Relevance
“…To date, only five fMRI studies have examined BSs ( 39 43 ). Studies examining cerebral activation in patients with schizophrenia consistently reported significant associations between BSs and localized decreased activations in the ventral premotor cortex ( 40 ) and in the left inferior parietal lobule during passive viewing of neutral actions ( 43 ). Notably, increased connectivity between ventral premotor cortex and posterior cingulate cortex was associated with the severity of BSs in first-episode schizophrenia patients ( 39 ).…”
Section: Basic Symptoms and Current Neurobiological Research In Psychmentioning
confidence: 99%
“…To date, only five fMRI studies have examined BSs ( 39 43 ). Studies examining cerebral activation in patients with schizophrenia consistently reported significant associations between BSs and localized decreased activations in the ventral premotor cortex ( 40 ) and in the left inferior parietal lobule during passive viewing of neutral actions ( 43 ). Notably, increased connectivity between ventral premotor cortex and posterior cingulate cortex was associated with the severity of BSs in first-episode schizophrenia patients ( 39 ).…”
Section: Basic Symptoms and Current Neurobiological Research In Psychmentioning
confidence: 99%
“…Such a reduced connectivity was absent in patients treated with antipsychotics, and negatively correlated with unusual thought content in untreated patients [52]. Right anterior insular deficit can also be linked to a deficit in understanding the emotional components of the actions of others [53]. The improvement of the anterior insular deficit has been related to clinical improvements obtained with antipsychotic treatment [54].…”
Section: Discussionmentioning
confidence: 99%
“…They tend to misinterpret the affective keys of the social context, which leads to alterations in SC and behaviour. 26 Once again, this type of limitation in emotional processing is likely to affect patients who are progressing towards their first episode. In fact, recent studies report that patients at this stage show serious defects in processing the emotional component of motor actions that activate the mirror neuron system.…”
Section: Processing Of Emotionsmentioning
confidence: 99%
“…In fact, recent studies report that patients at this stage show serious defects in processing the emotional component of motor actions that activate the mirror neuron system. 26…”
Section: Processing Of Emotionsmentioning
confidence: 99%